Studi Perbandingan Perilaku Balok Beton Tulangan Baja Konvensional dan Balok Beton Tulangan Glass Fiber Reinforced Polymer - Kharisma Dwi Ramadhani; Annisa Rahma Sabrina; M. Vicky Restu Bachtiar; Aviv Setiawan; Endah Kanti Pangestuti; Nurti Kusuma Anggraini (Jurnal Kridatama Sains dan Teknologi, 2026)
Reinforced concrete commonly uses conventional steel reinforcement due to its good tensile strength and ductility. However, steel reinforcement is susceptible to corrosion and has a relatively high self-weight. Glass Fiber Reinforced Polymer (GFRP) has emerged as an alternative reinforcement material with high tensile strength, low weight, and excellent corrosion resistance. This study aims to compare the flexural behavior of reinforced concrete beams using GFRP reinforcement and conventional steel reinforcement in terms of maximum flexural capacity, load–deflection behavior, and crack patterns. The research was conducted experimentally through laboratory testing using the two-point loading method. The test specimens were concrete beams measuring 150 × 150 × 600 mm, reinforced with either steel or GFRP bars with diameters of 6 mm and 8 mm. The results indicate that GFRP-reinforced beams exhibit higher maximum flexural capacity than steel-reinforced beams, with increases of 44.53% for 6 mm diameter bars and 15.65% for 8 mm diameter bars. In addition, GFRP-reinforced beams show greater deflection, indicating higher flexibility compared to steel-reinforced beams. Crack pattern observations reveal that GFRP-reinforced beams develop more numerous and widely distributed cracks and tend to experience shear failure, whereas steel-reinforced beams display more controlled flexural cracking. These findings suggest that GFRP reinforcement has significant potential as an alternative to conventional steel reinforcement, particularly for structures requiring high corrosion resistance and a high strength-to-weight ratio, while careful consideration of shear failure is necessary in design